Uremic Pruritis in Patients of End Stage Renal Disease on Thrice-Weekly Hemodialysis - Burki, Ayousha; Anwar, Shahid; Akram, Mateen; Awan, Abad-ur-Rehman; Usman, Hafiz Tahir; Anwar, Zahid (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of uremic pruritus in ESRD patients on thrice-weekly maintenance hemodialysis. Study Design: Cross-sectional analytical study Place and Duration of Study: Department of Nephrology, Sir Ganga Ram Hospital, Lahore from 1st Mar 2018 to 15th February 2019. Methodology: Sixty five adult patients on hemodialysis for >3 months duration were included whereas patients on hemodialysis for acute kidney injury duration <3 months and exhibiting clinical or laboratory features of other conditions as chronic skin disease, cholestasis, and malignancies were excluded from the study. Results: The mean age was 48±13.29 years, 46 (70.8%) were males and 19 (29.2%) were females. The mean BMI of patients was 23.73 kg/m2. Thirty one (47.1%) was diabetics and 34(52.9%) was nondiabetics. Hypertension was found in 61(93.9%) while 4(6.2%) were normotensive, 3 (4.6%) were on HD from 6 months to 1 year, while 19(29.4%), 43(66.0%) were on HD for 1 to 3 years and >3 years respectively. Conclusion: The frequency of uremic pruritis in patients on thrice-weekly MHD is 23.1% in our population.